Hypoxic mesenchymal stem cell‐conditioned medium accelerates wound healing by regulating IL‐10 and TGF‐β levels in a full‐thickness‐wound rat model - Adi Muradi Muhar; Faizal Mukharim; Dedy Hermansyah; Agung Putra; Nurul Hidayah; Nur Dina Amalina; Iffan Alif (Universitas Gadjah Mada, 2022)
Full‐thickness wound healing is a complex process requiring a well‐orchestrated mechanism of various factors, including cytokines, particularly interleukin (IL)‐10 and transforming growth factor (TGF)‐β. IL‐10 and TGF‐β act as robust anti‐inflammatory cytokines in accelerating the wound healing process by regulating myofibroblasts. Hypoxic mesenchymal stem cell‐conditioned medium (hypMSC‐CM) containing cytokines potentially contribute to accelerate wound repair without scarring through the paracrine mechanism. This study aims to observe the role of hypMSC‐CM in controlling TGF‐β and IL‐10 levels to accelerate full‐thickness wound repair and regeneration. A total of 24 male Wistar rats were used in this study. Six healthy rats as a sham group and 18 rats were created as full‐thickness‐wound animal models using a 6 mm punch biopsy. The animals were randomly assigned into three groups (n = 6) consisting of two treatment groups treated with hypMSC‐CM at a low dose (200 µL hypMSC‐CM with 2 g water‐based gel added) and a high dose (400 µL hypMSC‐CM with 2 g water‐based gel added) and a control group (2 g water‐based gel only). The IL‐10 and TGF‐β levels were examined by ELISA. The results showed a significant increase in IL‐10 levels on day 3 after hypMSC‐CM treatment, followed by a decrease in platelet‐derived growth factor (PDGF) levels on days 6 and 9. In line with this finding, the TGF‐β levels also increased significantly on day 3 and then linearly decreased on days 6 and 9. HypMSC‐CM administra‐ tion may thus promote wound healing acceleration by controlling IL‐10 and TGF‐β levels in a full‐thickness‐wound rat model.